Collaboration in Mitigating Forest and Land Fires in South Sumatra Province - Ramadhan, Muhammad Novrizal; Perdana, Dimes Akbar; Gulthom, Fahrian Arsyam; Zulfikar, Zulfikar; Khan, Aditya Sulthony Ahmad (Universitas Negeri Makassar, 2025)
Forest and land fires are one of the environmental problems that often occur in South Sumatra Province, because the existing peatland area is a potential threat to forest and land fires. This research focuses on the collaboration that occurs in South Sumatra Province in mitigating forest and land fires. There are several main points in this research, firstly how collaboration in mitigating forest and land fires in South Sumatra Province, secondly the mapping of stakeholders involved in mitigating forest and land fires. The approach to handling forest and land fires has undergone a paradigm shift, where from 2016 to 2023, collaboration and mitigation efforts have become the main focus. The collaboration established during this period has begun to show positive impacts, as reflected in the relatively controlled burned areas and haze levels between 2020 and 2023. However, it is also important to reassess these collaborative efforts from other perspectives, such as evaluation and effectiveness, considering that forest and land fires continue to occur to this day.